Transformasi Hukum Persaingan Usaha Digital untuk Kesejahteraan Konsumen dan Sustainable Development Goals - Banjarnahor, David (CV Rewang Rencang, 2026)
The transformation of competition law in the digital economy era is an urgent necessity amid rapid of information technology development reshaping Indonesia’s business landscape. The current legal framework fails to accommodate digital market traits like platform dominance, personal data management and new monopoly practices. This normative study examines needs for adaptive, consumer protection oriented and regulations fostering sustanaible development. Strengthening the role of the Business Competition Supervisory Commission, cross sectoral collaboration and adoption best practices from other countries are strategies in creating a healthy, fair and sustainable digital business ecosystem, legal transformation becomes an important foundation for comprehensive digital economic growth.